An evaluation of a simulation and video-based training program to address adverse childhood experiences. (September 2020) - Miller-Cribbs, Julie; Bragg, Jedediah; Wen, Frances; Jelley, Martina; Coon, Kim A; Hanks, Heather; Howell, Daniel; Randall, Ken; Isaacson, Mary; Rodriguez, Kristin; Sutton, Ginger
Adverse Childhood Experiences (ACEs) are multiple sources of maltreatment and household dysfunction with tremendous impact on health. A trauma-informed (TI) approach is preferred when working with patients with ACEs. The Professional ACEs-Informed Training for Health © (PATH © ) educational program and simulation experience using standardized patients (SP) was developed to help healthcare professionals address ACEs with adults. PATH © is a 3–4 hour curriculum comprised of lecture and discussion, video-based demonstration, simulation experience, and debriefing. It was first developed for primary care (PC) residents in family medicine and internal medicine, and subsequently modified for occupational therapy (OT) and physical therapy (PT) students. This study evaluates a preliminary dataset focusing on PATH © skills of PC residents and OT and PT students during simulation. Recordings of 53 learner-SP encounters from 15 OT and PT students and 38 PC residents were coded using standardized behavioral codes. A subset of ten recordings of PC residents who participated in simulations in the first and fourth year of the training program allowed for evaluation of training outcomes over time. Results showed that medical residents and OT and PT students demonstrated skills during SP encounters congruent with TI training on addressing ACEs with adults, particularly in explaining ACEs, demonstrating empathy, collaborative treatment planning, and stigma reduction. PC residents showed both positive and negative changes in PATH © -specific skills from year 1 to 4 of the training program. This study supports the PATH © model and simulation-based training in preparing clinicians to address ACEs with adults and provides insight into further curriculum improvement.